Optical polarization properties of the closest tidal disruption event AT 2023clx indicate origin from tidal stream shocks - Koljonen, Karri I. I.; Nilsson, Kari; Liodakis, Ioannis; Lindfors, Elina (Oxford University Press (OUP), 2026)
Polarization observations of tidal disruption events offer unique insights into the accretion processes around supermassive black holes. Here, we present optical polarization observations of the nearby event AT 2023clx, obtained using the Nordic Optical Telescope. Our observations reveal a rise and subsequent decay in the polarization degree, temporally offset from the peak of the optical light curve, reaching maximum intrinsic polarization degree of similar to 5 per cent. In addition, the polarization angle shifts by similar to 60 degrees-100 degrees between 6 and 20 d after the optical peak, remaining stable thereafter. Remarkably, the observed polarization variability closely resembles that of AT 2020mot, strongly suggesting a common mechanism for accretion disc formation in these events. The variability in both polarization degree and angle supports models in which tidal stream shocks drive the optical outburst during the accretion disc formation.